2004
DOI: 10.1007/s00221-004-2018-7
|View full text |Cite
|
Sign up to set email alerts
|

Serotoninergic-mediated inhibition of substance P sensitive deep dorsal horn neurons: a combined electrophysiological and morphological study in vitro

Abstract: Dorsal horn neurons that express the neurokinin 1 receptor (NK-1R) play an important role in nociceptive processing. The targetting of NK-1R neurons by serotoninergic (5-hydroxytryptamine, 5-HT) axons would provide a straightforward means to exert an inhibitory analgesic effect at spinal level. This study used single cell electrophysiology to analyse and correlate the responses of rat deep DH neurons in vitro to both 5-HT and the NK-1R agonist [Sar9,Met(O2)11]-substance P (SP). Subsequently a combination of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In addition to the electrophysiological characterization of cells, identity was confirmed at the end of a recording session by filling cells with biocytin by passing 500 ms pulses of 0.5 nA outward (hyperpolarizing) current (Chen et al ., 1996; Koyama et al ., 1998; Worsley et al ., 2005) through the microelectrode at 1 Hz for 5–10 min. The membrane potential was monitored throughout this procedure to ensure that penetration was maintained during filling.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the electrophysiological characterization of cells, identity was confirmed at the end of a recording session by filling cells with biocytin by passing 500 ms pulses of 0.5 nA outward (hyperpolarizing) current (Chen et al ., 1996; Koyama et al ., 1998; Worsley et al ., 2005) through the microelectrode at 1 Hz for 5–10 min. The membrane potential was monitored throughout this procedure to ensure that penetration was maintained during filling.…”
Section: Methodsmentioning
confidence: 99%
“…Serotonergic descending pathways from brainstem form an endogenous analgesic system. Electrophysiological data demonstrated that 5-HT induced inhibition on SP-sensitive (putative NK-1 receptor expressing) dorsal horn neurons in vitro [42]. We have found that 5-HT-LI terminals contact with NK1 receptor-LI somata and dendrites in the superficial dorsal horn.…”
Section: Discussionmentioning
confidence: 70%
“…The coexpression of two neuromodulators with opposite effects may enhance the modulation of communication signals in response to changes in social environment or reproductive condition. In other systems, serotonin and substance P often colocalize and regulate behavior and motor rhythms through divergent effects on neuronal excitability (Svensson et al, 2001;Ramirez and Viemari, 2005;Worsley et al, 2005). Furthermore, substance P acting on neurokinin-1 receptors can inhibit the release of serotonin, and serotonin can block the modulatory effects of substance P (Santarelli et al, 2001;Svensson et al, 2001;Gobbi and Blier, 2005).…”
Section: Interactions Of Serotonin With Hormones and Other Neuromodulmentioning
confidence: 99%